2022
DOI: 10.3389/fgene.2022.1001904
|View full text |Cite
|
Sign up to set email alerts
|

Ascertaining yield and grain protein content stability in wheat genotypes having the Gpc-B1 gene using univariate, multivariate, and correlation analysis

Abstract: The high performance and stability of wheat genotypes for yield, grain protein content (GPC), and other desirable traits are critical for varietal development and food and nutritional security. Likewise, the genotype by environment (G × E) interaction (GEI) should be thoroughly investigated and favorably utilized whenever genotype selection decisions are made. The present study was planned with the following two major objectives: 1) determination of GEI for some advanced wheat genotypes across four locations (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
(94 reference statements)
2
10
1
Order By: Relevance
“…Nonetheless, we identi ed three genotypes (Cervino, Tjalve, and Polkka) that combined a high level of PC (14-15%) with high stability. Different from our results, Tanin et al (2022) found no clear relationship between the level and stability of PC.…”
contrasting
confidence: 99%
“…Nonetheless, we identi ed three genotypes (Cervino, Tjalve, and Polkka) that combined a high level of PC (14-15%) with high stability. Different from our results, Tanin et al (2022) found no clear relationship between the level and stability of PC.…”
contrasting
confidence: 99%
“…As indicated by the outcomes of preceding research, the environmental influences were notably significant across diverse environmental conditions 7 , 16 , 52 , 58 . As anticipated, environments subjected to heat stress demonstrated a diminished mean grain yield compared to non-stressed environments 2 , 4 , 41 .Previous reports in India have documented the grain yield superiority of newly developed recombinant lines over commercial checks 16 , 40 , 59 . This suggested that the newly created recombinant lines outperformed over the commercial checks under heat stress situations.…”
Section: Discussionsupporting
confidence: 65%
“…The potential for creating heat tolerant wheat genotypes with superior grain yield and grain lling rate advantages over the current commercial checks in central India can be seen in the fact that a set of heattolerant advanced wheat lines used in this study had higher grain yields and grain lling rates than both the parents and commercial check. Grain yield advantage of newly developed recombinant lines over the commercial checks has been previously reported in India (Tanin et al 2022;Singh et al 2019;Sareen et al 2014). This suggested that the newly created recombinant lines outperformed the commercial checks under heat stress situations.…”
Section: Discussionmentioning
confidence: 75%